(untitled) (GAIMS Journal of Medical Sciences, 2026)
Medical textbooks once formed the intellectual backbone of medical education. Today, their place is increasingly challenged by PDFs, online resources, and AI-driven tools. This editorial explores whether the pursuit of digital convenience risks eroding the depth of understanding essential for safe clinical practice.